2011
DOI: 10.1161/circulationaha.110.983866
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary Hypertension in Heart Failure With Preserved Ejection Fraction

Abstract: Background-The prevalence of heart failure with preserved ejection fraction is increasing. The prognosis worsens with pulmonary hypertension and right ventricular (RV) failure development. We targeted pulmonary hypertension and RV burden with the phosphodiesterase-5 inhibitor sildenafil. Methods and Results-Forty-four patients with heart failure with preserved ejection fraction (heart failure signs and symptoms, diastolic dysfunction, ejection fraction Ն50%, and pulmonary artery systolic pressure Ͼ40 mm Hg) we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
183
3
6

Year Published

2013
2013
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 519 publications
(198 citation statements)
references
References 43 publications
6
183
3
6
Order By: Relevance
“…Originally, work from Takimoto et al6 demonstrated the beneficial effects of PDE5 inhibition showing sildenafil attenuated hypertrophy, decreased fibrosis, and restored LV relaxation kinetics in aortic‐banded mice. Several preclinical and clinical studies followed investigating various methods of preserving cGMP levels, with beneficial results 5, 9, 10, 15, 44, 45, 46. However, the sole multicenter study targeting this signaling in HFpEF, the RELAX trial (Effect of Phosphodiesterase‐5 Inhibition on Exercise Capacity and Clinical Status in Heart Failure with Preserved Ejection Fraction), reported equivocal results after testing the PDE5 inhibitor sildenafil 47.…”
Section: Discussionmentioning
confidence: 99%
“…Originally, work from Takimoto et al6 demonstrated the beneficial effects of PDE5 inhibition showing sildenafil attenuated hypertrophy, decreased fibrosis, and restored LV relaxation kinetics in aortic‐banded mice. Several preclinical and clinical studies followed investigating various methods of preserving cGMP levels, with beneficial results 5, 9, 10, 15, 44, 45, 46. However, the sole multicenter study targeting this signaling in HFpEF, the RELAX trial (Effect of Phosphodiesterase‐5 Inhibition on Exercise Capacity and Clinical Status in Heart Failure with Preserved Ejection Fraction), reported equivocal results after testing the PDE5 inhibitor sildenafil 47.…”
Section: Discussionmentioning
confidence: 99%
“…Outcomes are worse when PH complicates left heart disease and there are no specific treatments (1)(2)(3)(4). Further, in patients with left heart disease, therapies indicated for PAH, such as prostacyclins and endothelin receptor antagonists have been unsuccessful, while phosphodiesterase type 5 inhibitors have met with mixed results (5)(6)(7)(8)(9). Therefore, a great need exists to develop targeted therapies and to identify the patient population that can benefit.…”
Section: Methodsmentioning
confidence: 99%
“…Recently, treatment with sildenafil failed to reduce PA pressure or hemodynamic parameters in a HFpEF cohort 183. In contrast, a single‐center, placebo‐controlled, randomized trial reported significant improvements in PA pressure, RV function, and LV relaxation with sildenafil in patients with HFpEF and PH 184. In the absence of evidence‐based data, PDE5‐I cannot be recommended for the treatment of PH in HFpEF 185, 186, 187.…”
Section: Ph Phenotypementioning
confidence: 99%